Struktur Sintaksis dan Makna Semantik Ungkapan Tradisional sebagai Representasi Masyarakat Jawa - Tafrijiyah, Kaamilah (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2024)
This article aimed at describing syntactic structures and semantic meanings in Javanese traditional expressions that represent Javanese local wisdoms. The local wisdoms that were reflected in the Javanese traditional expressions were traditions and noble values used by Javanese society as life patrone managing the community behavior in the context of social and spiritual life. The Javanese traditional expressions were part of culture as they were formed from ideas, behaviors, and works of the Javanese society. Traditional expressions were rapidly growing among the community as advice, thoughts, and educations in life. The Javanese traditional expressions could be in the form of “bebasan”, “sanepa”, “pepindhan”, “saloka”, and “paribasan”. Data of this study were phrases, clauses, and sentences covered by the Javanese traditional expressions. The data of this research were taken from Kamus Ungkapan Bahasa Jawa 1990 released by the Department of Education and Culture, the Republic of Indonesia. This research employed a descriptive qualitative method. While the collected data were analyzed by using syntactic and semantic approaches. Findings of this study inferred that the language structures that construct the Javanese traditional expressions were in the form of phrases, clauses, and sentences. In addition, the semantic meanings contained in the Javanese traditional expressions represented the common characteristics and the behaviors of Javanese society.